PUBLIC PERCEPTION OF TELUK BETUNG SELATAN IN THE DEVELOPMENT OF CHINATOWN IN TELUK BETUNG SELATAN - Effendi, Nicholas; Pienrasmi, Hanindyalaila; Poyo, M Denu (Universitas Dharmawangsa Medan, 2025)
This study explores public perceptions of the Chinatown development in Teluk Betung Selatan, which has generated a range of responses, including both support and opposition. Perception in communication refers to the absorption of information through the senses, influenced by external stimuli, and can result in either positive or negative attitudes toward a given situation. In this context, community perceptions are shaped by the extent of their involvement, access to information, and experience of the development’s impact either directly or indirectly. This research employs a qualitative approach, using data collection techniques such as in-depth interviews with informants from various backgrounds, direct field observation to capture the ongoing social dynamics, and documentation of relevant records and literature to strengthen the empirical data. Data validity is ensured through source triangulation, which aims to confirm the accuracy, consistency, and credibility of information obtained from multiple sources. The collected data is analyzed through data reduction, data presentation, and conclusion drawing to provide a comprehensive picture of community perceptions.The findings indicate that the Chinatown development is perceived by some community members as an opportunity to boost the local economy, promote tourism, and revitalize the Teluk Betung Selatan area, which was previously considered underdeveloped. However, the study also reveals concerns among parts of the community regarding the potential loss of local identity due to the dominance of external cultural symbols that lack inclusive narratives. Additionally, the public highlighted the limited community involvement in the planning and decision-making processes, creating the impression that the project was executed in a top-down manner. This has contributed to negative perceptions of the development. These findings emphasize the importance of transparent communication, active community participation, and efforts to balance the preservation of local identity with urban development.